2014
DOI: 10.1016/j.nuclphysb.2013.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Logarithmic exotic conformal Galilean algebras

Abstract: International audienceLogarithmic representations of the conformal Galilean algebra (CGA) and the Exotic Conformal Galilean algebra (EcGA) are constructed. This can be achieved by non-decomposable representations of the scaling dimensions or the rapidity indices, specific to conformal Galilean algebras. Logarithmic representations of the non-exotic CGA lead to the expected constraints on scaling dimensions and rapidities and also on the logarithmic contributions in the co-variant two-point functions. On the ot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…In this way we have achieved the tensor density construction of the superalgebra sg ℓ : 15) where ⊕ denotes the direct sum of vector spaces. In order to discuss coadjoint representations, we would like to introduce the algebraic dual of sg ℓ .…”
Section: Tensor Density Module Construction Of Sg ℓ and Regular Dualmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way we have achieved the tensor density construction of the superalgebra sg ℓ : 15) where ⊕ denotes the direct sum of vector spaces. In order to discuss coadjoint representations, we would like to introduce the algebraic dual of sg ℓ .…”
Section: Tensor Density Module Construction Of Sg ℓ and Regular Dualmentioning
confidence: 99%
“…The same algebra appears in non-relativistic analogue of AdS/CFT correspondence and called infinite dimensional Galilean conformal algebra (GCA) [10,11,12,13,14,15] (see also [16,17,18,19,20,21] for some varieties of the algebra). The same algebra also appears in cosmological topologically massive gravity [22,2] and bosonic string theory [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Analogous representations can also be considered for the Schrödinger and conformal Galilean algebras and their sub-algebras. Then, it becomes necessary to consider simultaneously the scaling dimensions x, ξ and the rapidities γ as matrices [41,42,43,57,37]. From the Lie algebra commutators it can then be shown that these characteristic elements of the scaling operators are simultaneously Jordan [37].…”
Section: Examplementioning
confidence: 99%
“…Then, it becomes necessary to consider simultaneously the scaling dimensions x, ξ and the rapidities γ as matrices [41,42,43,57,37]. From the Lie algebra commutators it can then be shown that these characteristic elements of the scaling operators are simultaneously Jordan [37]. Several applications to non-equilibrium relaxation phenomena have been explored in the literature [34,35,44,22], see [36] for a review.…”
Section: Examplementioning
confidence: 99%
“…Such co-variant n-point functions arise for example in several distinct non-relativistic versions of the AdS/CFT correspondence, see e.g. [5,3,4,13,27,11,12,33,6,1,28,14,7,22] and refs. therein.…”
mentioning
confidence: 99%